Occurrence of brassinosteroids in non-flowering land plants, liverwort, moss, lycophyte and fern. (April 2017) - Yokota, Takao; Ohnishi, Toshiyuki; Shibata, Kyomi; Asahina, Masashi; Nomura, Takahito; Fujita, Tomomichi; Ishizaki, Kimitsune; Kohchi, Takayuki
Abstract: Endogenous brassinosteroids (BRs) in non-flowering land plants were analyzed. BRs were found in a liverwort ( Marchantia polymorpha ), a moss ( Physcomitrella patens ), lycophytes ( Selaginella moellendorffii and S. uncinata ) and 13 fern species. A biologically active BR, castasterone (CS), was identified in most of these non-flowering plants but another biologically active BR, brassinolide, was not. It may be distinctive that levels of CS in non-flowering plants were orders of magnitude lower than those in flowering plants. 22-Hydroxycampesterol and its metabolites were identified in most of the non-flowering plants suggesting that the biosynthesis of BRs via 22-hydroxylation of campesterol occurs as in flowering plants. Phylogenetic analyses indicated that M. polymorpha, P. patens and S. moellendorffii have cytochrome P450s in the CYP85 clans which harbors BR biosynthesis enzymes, although the P450 profiles are simpler as compared with Arabidopsis and rice. Furthermore, these basal land plants were found to have multiple P450s in the CYP72 clan which harbors enzymes to catabolize BRs. These findings indicate that green plants were able to synthesize and inactivate BRs from the land-transition stage. Graphical abstract: Castasterone, 22-hydroxycampesterol, and other brassinosteroids were identified and quantified in non-flowering plants. Homologs of Arabidopsis P450 enzymes involved in brassinosteroid biosynthesis and catabolism are phylogenetically analyzed in a liverwort, moss and lycophyte. Highlights: Brassinosteroids occur in liverwort, moss, lycophyte and fern species examined. Castasterone may be a biologically active brassinosteroid in these plants. Castasterone may be synthesized from 22-hydroxycampesterol as in flowering plants. Liverwort, moss and lycophyte species here have cytochrome P450s in the CYP85 and CYP72 clans. The P450s in the CYP85 clan in the lower plants are at middle stages of evolution.